Combined effect of microRNA, nutraceuticals and drug on pancreatic cancer cell lines. (25th May 2015) - Pandita, Archana; Manvati, Siddharth; Singh, Shashank K.; Vaishnavi, Samantha; Bamezai, Rameshwar N.K.
Highlights: Decreased cellular viability with combination of miRNAs, drug and dietary molecules. Enhanced apoptosis and synergetic effect observed in selected combinations. Overexpressing miR-101 MIA PaCa-2 cells show enhanced apoptosis and synergism. Overexpressing miR-24-2 PANC-1 cells show enhanced apoptosis and synergism. Results suggest therapeutic potential of the identified combinations. Abstract: Aim: We proposed to investigate the combination effect of microRNA, nutraceuticals and drug (MND), in two pancreatic cancer cell lines to assess the therapeutic potential. Materials and methods: MIA PaCa-2 and PANC-1 cells transfected with miR-101 or miR-24-2 were treated with Betulinic acid or Thymoquinone and gemcitabine independently and in combination and assessed for the extent of synergism in both experimental and control conditions, considering significance at the p value of <0.05. Results: miR-101 or miR-24-2 over-expressing cells when treated with lower than IC50 doses of the dietary compounds and drug showed a reduced (37–50%) viability in two cell lines with differential synergistic effect and the outcome for Pro-caspase3, Poly (ADP-ribose) polymerase (PARP) cleavage and PKM2 expression. Conclusion: Two independent microRNA backgrounds showed promise in therapeutic intervention of gemcitabine sensitive, MIA PaCa-2 and resistant, PANC-1 pancreatic cancer cells, in combination with dietary agents and drug.